Pengaruh Manajemen Kelas Inklusif terhadap Prestasi Belajar Siswa Sekolah Dasar - Muhammad Ziaulhaq; Nurnaningsih Nurnaningsih; Silaturrahmih Silaturrahmih; Nur Komalasari; Venna Oktavia (Bima Journal of Elementary Education, 2024)
In the current educational context, the effectiveness of inclusive classroom management in improving student learning achievement in elementary schools has become an urgent topic for research. This study aims to analyze the influence of inclusive classroom management on student learning achievement, considering variables such as adaptive teaching strategies, support for the learning environment, and dynamics of student interaction. Using quantitative methods with a survey research design, this study involved a sample of 40 elementary school students from the city of Bima, selected through purposive sampling technique, considering the specific characteristics of the population studied. Data were collected using questionnaires and analyzed using descriptive statistics and linear regression tests to determine the impact of inclusive classroom management on learning achievement. The results show a significant positive effect of inclusive classroom management on student learning achievement, reaffirming the importance of adapting teaching strategies and creating a supportive learning environment in inclusive classrooms. This conclusion supports the argument that effective inclusive classroom management practices are essential for improving student learning outcomes. Based on these findings, this study recommends enhancing teacher capacity through continuous professional training in inclusive classroom management and the development of a more inclusive curriculum to support the learning success of all students.